The Influence Of Location, Promotion And Lifestyle On Purchasing Decisions Inkampoeng Hijrah Residence Tasikmalaya Housing - Rizky Muhammad Nur Syiroj; Suci Putri Lestari; Arga Sutrisna (Journal of Indonesian Management, 2023)
The purpose of this study was to find out the influence of location, promotion and lifesyle simultaneously and partially on survey housing purchase decisions on Kampoeng Hijrah Reasidence, Tasikmalaya. The research method used is a quantitative method with a causality survey approach. The sample in the study was 61 respondents. Data collection is done using questionnaries. The data analysis used is multiple regression analysis. The result of this study showed simultaneously the location, promotion and lifesyle gave a significant influence on housing purchasing decisions. Partially location, promotion and lifestyle, each has a positive and significant effect on purchasing decisions.